Optimization of process parameters for treatment of pulp and paper mill waste water with Fecl3 and iron nanoparticles - PRATIBHA SINGH; NOOPUR SRIVASTAVA; DIVYA GHILDYAL (International Journal of Pharma and Bio Sciences, 2018)
The pulp and paper industry waste water is highly polluted due to its dark color, foul odour, high organic content & extreme quantities of COD, BOD & chlorinated compounds. These toxic impurities are removed by chemical precipitation using ferric chloride and iron nanoparticles at various concentrations. Today iron nanoparticles used for detection and removal of chemical and biological substances include metals, nutrients and chlorinated organic compounds. Iron nanoparticles have shown effective results than other chemical techniques used in pulp and paper mill effluent treatment. Iron nanoparticles are widely used in contaminated chlorinated organic compounds. In the current study two samples of pulp & paper mill effluent treated with FeCl3 & iron nanoparticles at various concentration and process conditions were taken and it has beenobserved that the concentration of FeCl3 in the sample was high but treatment was less effective while the concentration of iron nanoparticles used in other sample was very low but the treatment was very effective. Optimization of parameters study has been conducted to establish ideal condition for treatment. Iron nanoparticles are extremely reactive because of their large surface area, In the presence of oxygen & water they rapidly oxidize to form free iron ions and this treatment process is comparatively environmental friendly giving results which can be used in future studies to remove toxic compounds.